Answer:
Dilation of 3
Step-by-step explanation:
Answer:
Divide by 2
q^2+4q=3/2
q^2+4q(4/2)^2=3/2+(4/2)^2
(q+4/2)^2=3/2+16/4
taking the square root of both side
√(q+4/2)^2=√(3/2+16/4)
Note that the square will cancel the square root then you will take LCM on the right hand side
q+4/2=√6+16/4
q+4/2=√22/4
q= -4/2+-√22/4
q=(-4+_√22/4)
Answer:
(3x - 5 = -x + 3) x = 2
Step-by-step explanation:
3x - 5 = -x + 3
3x = -x + (3 +5)
3x=-x + 8
(3x + x ) = 8
4x = 8
4/8 =2
x = 2
f(x) = (x + 5)(x - 1)
using the ' factor theorem '
given x = a is the root of a polynomial then (x - a ) is a factor
here roots are x = - 5 and x = 1 hence factors are (x + 5) and (x - 1)
the polynomial is the product of the factors
f(x) = (x + 5)(x - 1)
Answer:
the frist one
Step-by-step explanation:
the geart answer